Analysis of The Impact of Rainfall and Temperature on Rice Productivity in The Pamona Puselemba District of Poso Regency, Central Sulawesi - Eferson Julio Tadjodja; Widyastuti Widyastuti; Dwi Juli Puspitasari; Suwarni Suwarni (JPG (Jurnal Pendidikan Geografi), 2026)
Changes in rainfall patterns and increased temperatures are climate phenomena that will affect agricultural activities, especially rice farming. The purpose of this study is to analyze the impact of rainfall and temperature on rice productivity using multiple linear regression analysis in Pamona Puselemba District, Poso Regency. Data collection techniques were carried out through literature studies, document studies, and interviews. Based on the results of the study, the independent variables, namely rainfall and temperature, have a negative effect on rice production. This can be seen from the regression coefficient values in the analysis results, which show that for rice production, the rainfall variable has a value of -2.825 and the temperature variable has a value of -10784.004. However, the rainfall variable does not have a significant effect, because its significance value is 0.066 > 0.05, while the temperature variable has a significant effect with a significance value of 0.008 < 0.05. Rainfall and temperature also have a negative effect on the area of rice fields, as seen from the regression coefficient, where the rainfall variable has a value of -0.925 and the temperature variable has a value of -2304.966. The variables of rainfall and temperature both have a significant effect on land area, as shown by the significance value of rainfall of 0.020 < 0.05 and the temperature variable of 0.006 < 0.05. Interviews with farmers also showed that rainfall and temperature affect rice productivity, such as the rainy season and long dry seasons which reduce rice/grain production, lower the quality of the harvest, increase pest and disease attacks, and even affect processing methods and the use of certain rice varieties.